Інформаційна безпека сучасного бухгалтерського обліку - Ілляшенко, Катерина Володимирівна; Илляшенко, Екатерина Владимировна; Illiashenko, Kateryna (My University, 2019)
UK: У публікації розглянуто питання впливу інформаційних технологій на економічну безпеку діяльності підприємства в сучасних умовах господарювання. Досліджено найбільш поширені підходи до визначення економічної безпеки підприємства. Висвітлено поняття «інформаційні загрози» та «інформаційна безпека» як окремі категорії, що найбільш притаманні автоматизованим виробничим та обліково-аналітичним процесам. Визначено види інформаційного ризику як у конкретних випадках, так і у широкому контексті інформаційної безпеки. Проаналізовано рівень ризиків інформаційної загрози та способи їх оцінки. Обґрунтовано доцільність інформаційної безпеки під час ведення бухгалтерського обліку з використанням комп’ютерних технологій. Запропоновано заходи щодо попередження ймовірних інформаційних небезпек для обліково-аналітичної діяльності. RU: В публикации рассмотрены вопросы влияния информационных технологий на экономическую безопасность деятельности предприятия в современных условиях хозяйствования. Исследованы наиболее распространенные подходы к определению экономической безопасности предприятия. Освещены понятия «информационные угрозы» и «информационная безопасность» в качестве отдельных категорий, наиболее свойственных автоматизированным производственным и учетно-аналитическим процессам. Определены виды информационного риска как в конкретных случаях, так и в широком контексте информационной безопасности. Проанализированы уровень рисков информационной угрозы и способы их оценки. Обоснована целесообразность информационной безопасности при ведении бухгалтерского учета с использованием компьютерных технологий. Предложены меры по предупреждению вероятных информационных опасностей для учетно-аналитической деятельности. EN: The purpose of the study is to consider the impact of information technology on the economic security of the enterprise, the analysis of information risks for accounting and the search for measures to prevent possible information hazards. The formation of the information society conceptually and practically means the creation of a new worldview in which protection from information threats will be very important. The article discusses the impact of information technology on the economic security of the enterprise in modern economic conditions. The most common approaches to the definition of economic security of the enterprise are investigated. The concepts of «information threats» and «information security» as separate categories, the most characteristic of automated production and accounting and analytical processes, are highlighted. The types of information risk, both in specific cases and in the broad context of information security, are defined. The level of risks of information threat and ways of their estimation are analyzed. The expediency of information security in accounting with the use of computer technologies is substantiated. It was agreed that the issues of information security in accounting with the use of computer technology should be considered in two aspects: prevention of abuse or unintentional violations by employees of the enterprise (internal aspect) and the creation of appropriate information security to prevent unauthorized access, damage to computer programs or data viruses, computer sabotage (external aspect).The measures on prevention of danger for information that serves for accounting and analytical activity are offered, such as possible methods of reduction of information risk, formation of a new approach to enterprise management, protection of internal information from external interference, analysis of information risks at decision-making of management decisions. is concluded that the formation of a new approach to information security of accounting requires a review of personnel issues, new forms of control and mandatory accounting of factors characteristic of the new digital economy.
Information security of modern accounting
Keywords: інформація; інформаційні технології; безпека; підприємство; ризики; діяльність; бухгалтерський облік; информация; информационные технологии; безопасность; предприятие; риски; деятельность; бухгалтерский учет; information; information technology; security; enterprise; risks; activities; accounting